Scattering of internal waves by vertical barrier in a channel of stratified fluid - Dolai, Prity (Zielona Góra: Uniwersytet Zielonogórski)
The problem of two dimensional internal wave scattering by a vertical barrier in the form of a submerged plate, or a thin wall with a gap in an exponentially stratified fluid of uniform finite depth bounded by a rigid plane at the top, is considered in this paper. Assuming linear theory and the Boussinesq approximation, the problem is formulated in terms of the stream function. In the regions of the two sides of the vertical barrier, the scattered stream function is represented by appropriate eigen function expansions.
Keywords: stratified fluid; internal wave; vertical barrier; stream function; scattering matrix; Boussinesq approximation; eigen function expansion